Measurement of D⁎±, D± and D±s meson production cross sections in pp collisions at √s = 7 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Nuclear physics. B, Particle physics, 2016)
The production of D⁎±, D± and Ds± charmed mesons has been measured with the ATLAS detector in pp collisions at s=7 TeV at the LHC, using data corresponding to an integrated luminosity of 280 nb−1. The charmed mesons have been reconstructed in the range of transverse momentum 3.5<pT(D)<100 GeV and pseudorapidity |η(D)|<2.1. The differential cross sections as a function of transverse momentum and pseudorapidity were measured for D⁎± and D± production. The next-to-leading-order QCD predictions are consistent with the data in the visible kinematic region within the large theoretical uncertainties. Using the visible D cross sections and an extrapolation to the full kinematic phase space, the strangeness-suppression factor in charm fragmentation, the fraction of charged non-strange D mesons produced in a vector state, and the total cross section of charm production at s=7 TeV were derived.